2019
DOI: 10.31557/apjcp.2019.20.12.3667
|View full text |Cite
|
Sign up to set email alerts
|

Behavior and Food Consumption Pattern of the French Polynesian Population in the 1960s –1970s

Abstract: Background. Reconstruction of radiation doses to the thyroid for a case-control study of thyroid cancer in French Polynesians exposed to radioactive fallout from atmospheric nuclear weapons tests during childhood and adolescence faced a major limitation on very little availability of information on lifestyle of French Polynesians in the 1960s-1970s. Method: We use the focus group discussion and key informant interview methodology to collect historical, for the 1960s-1970s, data on behavior and food consumption… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
22
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

4
0

Authors

Journals

citations
Cited by 4 publications
(22 citation statements)
references
References 10 publications
0
22
0
Order By: Relevance
“…A detailed description of the methods used to calculate thyroid doses for the populations of these islands can be found elsewhere (Drozdovitch et al, 2021). Behaviour and age-specific consumption rates of cow's milk by residents of Fiji and Samoa were assumed to be the same as those for population of Tahiti (Drozdovitch et al, 2019).…”
Section: Time Of Arrival Of Falloutmentioning
confidence: 99%
See 1 more Smart Citation
“…A detailed description of the methods used to calculate thyroid doses for the populations of these islands can be found elsewhere (Drozdovitch et al, 2021). Behaviour and age-specific consumption rates of cow's milk by residents of Fiji and Samoa were assumed to be the same as those for population of Tahiti (Drozdovitch et al, 2019).…”
Section: Time Of Arrival Of Falloutmentioning
confidence: 99%
“…For Fiji (Suva), Samoa (Apia), Tonga (Tongatapu) and Cook Islands (Rarotonga) thyroid doses were estimated 1966 1967 1968 1970 1971 1972 1973 1974 (AWTSC, 1971(AWTSC, -1974 and thyroid doses due to 131 I intake with cow's milk for 1-y old child from Australia (Gibbs et al, 1967(Gibbs et al, -1969AWTSC, 1971-1974), New Zealand (UNSCEAR, 1977, South America and Madagascar (RF, 1967(RF, -1975 with those from Tahiti (Drozdovitch et al, 2021). Thyroid doses due to 131 I intake with cow's milk, which were taken from AWTSC and RF reports, were calculated for daily consumption of cow's milk by 1-y old child of 0.7 L for Australia, South America and Madagascar; daily consumption of cow's milk for Tahiti was 0.37 L (Drozdovitch et al, 2019).…”
Section: Dose Estimatesmentioning
confidence: 99%
“…To overcome these limitations, a special study was conducted in French Polynesia in 2016-2017 to collect historical behavior and dietary habits of the French Polynesia population in the 1960s-1970s using focus-group discussions and key-informant interviews. Detailed description and results of the focus-group study can be found elsewhere (Drozdovitch et al 2019a).…”
Section: Introductionmentioning
confidence: 99%
“…As mentioned above, the TD08 model was substantially improved with data on behavior and food consumption of the population in the 1960s-1970s, which was collected in all archipelagos of French Polynesia using focus-group discussions and key-informant interviews (Drozdovitch et al 2019a). The data collected during the focus-group study were used in TD19 in the following way:…”
mentioning
confidence: 99%
See 1 more Smart Citation